Pengaruh Variasi Temperatur Terhadap Kuantitas Char Hasil Pirolisis Serbuk Kayu Mahoni (Switenia Macrophylla) Pada Rotary 39 Kiln - Qiram, Ikhwanul; Widhiyanuriyawan, Denny; Wijayanti, Widya (Jurnal Rekayasa Mesin, 2015)
Pirolysis is thermochemical decomposition process of biomass into useful product. One kind of method that can be used is a Rotary Kiln pirolyzer which is consist a heating cylinder that rotates with a certain rotation speed. This research is aimed to get the effect of temperature due to Char product quantity of switenia macrophylla Rotary Kiln pirolysis.The research has done by pirolysis experiment with 200 gram of switenia macrophylla in dust form. Temperature was varied 250 C, 350 o C, 450 o C, 500 o C, and 600 C. The heating temperature was provided by eletric heater with control system. Temperatur was measured with K type thermocouple. The heating process has taken for 180 minutes using stopwatch. The measurement has done for biomass and Char volume using measuring cup. Mass was measured by using mass scale. Low heating value was measured by using bomb calorimeter. The result show that the temperature has effect due to Char product of switenia macrophylla Rotary Kiln pirolysis. The loss of Char mass is tend to increase due to temperature increases. Low heating value and Char porosity is tend to increase due to mass loss percentage increases. Shrinking factor and percentage of yield energy is tend to decrease due to mass loss percentage increasing.